2012
DOI: 10.2106/jbjs.k.01453
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Evidence in Foot and Ankle Surgery Literature: Progress from 2000 to 2010?

Abstract: There has been a trend toward higher levels of evidence in foot and ankle surgery literature over a decade, but the differences did not reach significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 15 publications
7
51
2
Order By: Relevance
“…This is in contrast to LOE improvement demonstrated among orthopaedic publications [12,21,33] and other subspecialties [18,41,50].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This is in contrast to LOE improvement demonstrated among orthopaedic publications [12,21,33] and other subspecialties [18,41,50].…”
Section: Discussioncontrasting
confidence: 78%
“…Since 2001, the LOE of clinical research presented at the AAOS and OTA annual meetings has increased [41,46]. Over this same time period, multiple orthopaedic subspecialty journals have demonstrated an increased emphasis on high-level study design and have subsequently increased the average LOE of articles published [10,18,21,29,33,50]. It was not known whether the research presented at the leading North American orthopaedic oncology meeting had kept pace with the changes observed in other orthopaedic subspecialties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are not unique in the orthopaedic literature. In their review of the Foot and Ankle literature from 2000 to 2010, Zaidi et al [38] showed a similar preponderance of observational studies with Level III to V data comprising over 89% of the published literature in that field. Samuelsson et al [28] identified in their review of ACL reconstruction studies that Level III to V studies made up 81% of all reports between 1995 and 2011.…”
Section: Discussionmentioning
confidence: 94%
“…Retrospective controlled studies were graded as Level III and retrospective uncontrolled studies were classified as ''case series'' and graded Level IV [36]. Case reports were included in the analysis and graded as Level V [13,38].…”
Section: Levels Of Evidencementioning
confidence: 99%